2011
DOI: 10.1021/jp2015534
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water and Temperature on Absorption of CO2 by Amine-Functionalized Anion-Tethered Ionic Liquids

Abstract: Amine-functionalized anion-tethered ionic liquids (ILs) trihexyl(tetradecyl)phosphonium asparaginate [P(66614)][Asn], glutaminate [P(66614)][Gln], lysinate [P(66614)][Lys], methioninate [P(66614)][Met], prolinate [P(66614)][Pro], taurinate [P(66614)][Tau], and threoninate [P(66614)][Thr] were synthesized and investigated as potential absorbents for CO(2) capture from postcombustion flue gas. Their physical properties, including density, viscosity, glass transition temperature, and thermal decomposition tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
226
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(230 citation statements)
references
References 32 publications
(109 reference statements)
2
226
0
2
Order By: Relevance
“…To increase their CO 2 absorption capacities, ILs need to be modified in such a way that the chemical absorption of CO 2 becomes accessible. The introduction of amine groups in the cation [18] or anion [19][20][21] is one of the easiest and most straightforward methods among the different strategies developed for the enhancement of CO 2 capacity. [22][23][24][25][26][27][28] Amino acid ionic liquids (AAILs) are particular representatives of amine-functionalized ILs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To increase their CO 2 absorption capacities, ILs need to be modified in such a way that the chemical absorption of CO 2 becomes accessible. The introduction of amine groups in the cation [18] or anion [19][20][21] is one of the easiest and most straightforward methods among the different strategies developed for the enhancement of CO 2 capacity. [22][23][24][25][26][27][28] Amino acid ionic liquids (AAILs) are particular representatives of amine-functionalized ILs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, lower temperatures or higher CO 2 partial pressures [21,38,39] shift the equilibrium towards 1:1 capacity. [20,21,38,39] Similarly, the attachment of the amine group to the anion instead of to the cation provides higher capacities. [18][19][20][21] Changing the location of the CO 2 absorption from the bulk to the surface of an IL with an amine-functionalized anion also increases the CO 2 capacity to 1:1 at a moderate CO 2 pressure.…”
Section: Introductionmentioning
confidence: 99%
“…It was seen (Supporting Information, Figure S4) that CO 2 capacity reduced about 0.1 mol per mol IL using moist CO 2 , where water may be preferentially absorbed, and the absorption rate using moist CO 2 increased significantly because of the decrease in the viscosity during CO 2 absorption. [14] Clearly, these pyridine-containing anion-functionalized ILs exhibit very high capacity for CO 2 capture by functionalized ILs and some other adsorbent materials (Supporting Information, Table S2). Why do these ILs exhibit such high capacities for CO 2 capture?…”
mentioning
confidence: 99%
“…The results showed lower performance by these IL membranes, however, the work conveyed an important concept about IL which have reactive amino groups capable to work as CO 2 carrier. Another study reported that tetrabutylphosphonium glycine ([P(C 4 ) 4 ][Gly]) has a very attractive CO 2 absorption capacity [56,57]. More surprisingly, [P(C 4 ) 4 ][AA]s have high CO 2 uptake capacity in both dry and humid conditions.…”
Section: Fixed-site-carrier (Fsc) Membranesmentioning
confidence: 99%